Man and ANA help mangroves in Philippines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Mangroves are a precious asset, providing protection against coastal erosion and shelter for fish and shellfish, and a source of wood (see Spore 82). The issue is how to get the best out of mangroves without destroying them, and in the Philippines...